Collectivism and citizenship in the social interaction of the Russian employee - Grachev, Alexandr A. (Saratov State University, 2024)
The relevance of the research consists in discussing the concepts of collectivism and citizenship as phenomena of social interaction of an employee, which is essential for both social and organizational psychology. The research objective is to substantiate a model of social interaction of an employee in which collectivism and citizenship act as phenomena of social interaction. Main results: The employee’s collectivism is understood in the proposed model as the employee’s orientation towards satisfying the interests of the interaction partner. Moreover, in the case of mutual collectivism, interaction takes place in the form of cooperation. In accordance with the three types of the employee’s interaction, their collectivism can be scarce (bring practical benefi ts), self-realization (bring joy), and spiritual (take the form of service). Taking into account the division of collectivism into two types (horizontal and vertical) and the three types of interaction, the study defi nes six types of collectivism. At the same time, the collectivism of an employee in an organization has its own peculiarities, depending on both their psychological characteristics and the type of organizational culture. Collectivism of the Russian employee is expressed and mainly takes the form of spiritual horizontal collectivism; that is the desire of the employee to help their colleagues selfl essly. The citizenship of an employee (readiness for civic behavior) is understood as one of the manifestations of collectivism – spiritual collectivism (willingness to sacrifi ce one’s interests for the sake of the interests of Another person - a colleague, a subordinate, a supervisor, a primary group, or an organization). Conclusions: The study substantiates a three-component model of the employee’s social interaction. This model makes it possible to single out six types of collectivism and to defi ne citizenship as spiritual collectivism. The specifi city of the collectivism of the Russian employee is defi ned as the expression of spiritual collectivism. Practical significance: The proposed model allows us to develop a) methods for assessing the employee’s orientation to interaction, b) techniques of developing the employee’s collectivism and citizenship.